2020
DOI: 10.3390/ijms21228561
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Regulation of Mesenchymal Stem Cell Migration by Various Chemotactic Stimuli

Abstract: Endogenous bone marrow-derived mesenchymal stem cells are mobilized to peripheral blood and injured tissues in response to changes in the expression of various growth factors and cytokines in the injured tissues, including substance P (SP), transforming growth factor-beta (TGF-β), and stromal cell-derived factor-1 (SDF-1). SP, TGF-β, and SDF-1 are all known to induce the migration of bone marrow-derived mesenchymal stem cells (BM-MSCs). However, it is not yet clear how these stimuli influence or interact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The main ones involved in the chemotactic process are chemokines and their receptors, pro-inflammatory cytokines, and growth factors. 75 Chemokines and their receptors mainly include CXCR1-6, CCR1/2/4/6/8/9, MCP-1, MIP-1α, and SDF-1. Pro-inflammatory cytokines such as IL-3, IL-6, IL-8, IL-1β, TGF-β, IGF-1, and TNF-α, as well as growth factors such as VEGF, PDGF, EGF, FGF, HGF, IGF, and SCF, are released from the site of injury to provide chemotaxis signals for MSCs to attract them to the designated location.…”
Section: Factors Influencing the Homing Processmentioning
confidence: 99%
“…The main ones involved in the chemotactic process are chemokines and their receptors, pro-inflammatory cytokines, and growth factors. 75 Chemokines and their receptors mainly include CXCR1-6, CCR1/2/4/6/8/9, MCP-1, MIP-1α, and SDF-1. Pro-inflammatory cytokines such as IL-3, IL-6, IL-8, IL-1β, TGF-β, IGF-1, and TNF-α, as well as growth factors such as VEGF, PDGF, EGF, FGF, HGF, IGF, and SCF, are released from the site of injury to provide chemotaxis signals for MSCs to attract them to the designated location.…”
Section: Factors Influencing the Homing Processmentioning
confidence: 99%
“…Other growth factors, such as glial cell-derived neurotrophic factor (GDNF) [22] and insulin-like growth factor-binding protein 5 (IGFBP5), promoted DPSC migration and enhanced the osteo/odontogenic and neurogenic differentiation of DPSCs [43]. Injured tissues can secrete the neuropeptide substance P (SP), which may exert immunomodulatory and stem cell recruitment roles [118,119]. Very recently, SP has been implicated in the odontoblastic differentiation of DPSCs during the reparative genesis of dentin.…”
Section: The Hdpsc Fatementioning
confidence: 99%
“…Similarly, TNF-α preconditioned MSC could better migrate in vitro toward selected chemokines such as the above-mentioned SDF-1, but this effect could not be correlated to CXCR4 expression levels[ 93 ]. In parallel, migration of MSC was also shown to be enhanced by exposure to transforming growth factor beta (TGF-β)[ 94 ], even though, in other studies[ 95 ], the same cytokine was also shown to downregulate migration of MSCs in response to SDF-1 stimuli. Interestingly, pre-exposure of MSC to TGF-β resulted in enhanced CXCR4 mediated migration toward glioblastoma cells[ 96 ].…”
Section: Msc Homing Improvement Strategiesmentioning
confidence: 99%